MAKANAN ADAT PADA UPACARA MANJALANG RUMAH MINTUO DI KANAGARIAN BTIPUAH BARUAH KECAMATAN BATIPUAH KABUPATEN TANAH DATAR - ANDRIANI, CICI; Baidar, Baidar; Sofnitati, Sofnitati (Journal of Home Economics and Tourism, 2014)
This research is that now people Batipuah Baruah in determining and processing of foodÂ  there is not book that used as a source of guidance, sometimes there are mistakes and disagreements between mothers of event to determine the type traditional foods, the quantity traditional food, the tools used and the meaning of traditional food. This research is purposed to (1) describes the implementation of a series of traditional ceremonies,(2) identification types of traditional food, (3) describe the equipment used to bring traditional food,(4) to explaning the meaning of traditional food brought on Manjalang Home Mintuo. The type of research is qualitative, and object of research is traditional food Manjalang Home Mintuo in Kanagarian Batipuah Baruah, data collected by Snow-Ball Sampling technique.Data analyzing include reduction, display and verification. Results showed that the manjalang home mintuo in Kanagarian Batipuah Baruah was conducted one day after the party wedding. The series of events Manjalang Home Mintuo in Kanagarian Batipuah Baruah has two stages: preparation before the event manjalang mintuo and a series of traditional ceremonies manjalang home mintuo. Keywords : tradisional food home manjalang mintuo